Meta Analysis: The Effect of The Geogebra Applet-Assisted Discovery Learning Model on Students’ Mathematical Problem Solving Ability in Geometry Material - Noverianto, Bebyd; Agoestanto, Arief; Dewi, Nuriana Rachmani; Mariani, Scolastika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Good mathematical problem solving skills are important for students because they are the goals and principles in learning mathematics. However, various studies, both national and international, state that students' mathematical problem solving abilities in Indonesia are still low. The Geogebra-assisted discovery learning model is an innovation that can be used to improve students' mathematical problem solving abilities. This research aims to analyze the influence of the Geogebra-assisted discovery learning model on students' mathematical problem solving abilities in geometry learning. The research method used is meta analysis. The articles analyzed are articles sourced from Scopus, ScienceDirect and Google Scholar with a period of 2013-2023. Of the 10 articles analyzed, 3 of them studied groups of middle school students, 4 groups of high school students, and 3 students. The results showed that 8 articles had a large effect size, 1 article was a medium size, and 1 article was a small size. The results of the Independent Sample t-test obtained tcount of 11.59 and ttable of 1.96. So it can be concluded that the discovery learning model assisted by Geogebra has an effect on students' mathematical problem solving abilities in geometry learning. Through the discovery model, students discover their own concepts and solve the problems. Geogebra is important for illustrating geometric problems. Future research can also analyze the extent of the influence of the Discovery Learning model assisted by Geogebra on students' mathematical problem solving abilities in terms of various other variables both from within the students and from the surrounding environment.